2021
DOI: 10.1111/ijcp.14865
|View full text |Cite
|
Sign up to set email alerts
|

External validation and comparison of two versions of simplified sequential organ failure assessment scores to predict prognosis of septic patients

Abstract: Background Evidence shows that simplified SOFA scoring system has better clinical practice. Objective This study aimed to validate and compare the scores acquired with simplified organ dysfunction criteria optimized for electronic health records (eSOFA), and simplified and accurate sequential organ failure assessment (sa‐SOFA) for their accuracies in predicting the prognosis of septic patients. Methods This retrospective observational study was conducted at three major academic hospitals. Clinical data from 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Eight studies [8,12,15,17,20,24,30,35] were prospective studies and the others [13, 14, 16, 18, 19, 21-23, 25-29, 31-34, 36] were retrospective studies. Five studies [12,15,23,24,33] were multi-center studies, and the others [8, 13, 14, 16-22, 25-32, 34-36] were described as single-center. The average age varied between 57 and 81, and the proportion of men varied between 46% and 65% in these studies.…”
Section: Search Results and Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies [8,12,15,17,20,24,30,35] were prospective studies and the others [13, 14, 16, 18, 19, 21-23, 25-29, 31-34, 36] were retrospective studies. Five studies [12,15,23,24,33] were multi-center studies, and the others [8, 13, 14, 16-22, 25-32, 34-36] were described as single-center. The average age varied between 57 and 81, and the proportion of men varied between 46% and 65% in these studies.…”
Section: Search Results and Description Of Studiesmentioning
confidence: 99%
“…Except for the study of Brink, et al [14], all other studies included consecutive or random cases, avoiding inappropriate exclusion. Because the cut-off values of the 11 studies [8,16,17,25,26,28,[32][33][34][35][36] were not determined in advance, there were high risks in the index test. Dick's funnel plot suggested that there was no publication bias (Fig 2 ).…”
Section: Quality Assessment Of Studiesmentioning
confidence: 99%